2016
DOI: 10.1161/circulationaha.115.019552
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter Regarding Article, “Facility Level Variation in Hospitalization, Mortality, and Costs in the 30 Days After Percutaneous Coronary Intervention: Insights on Short-Term Healthcare Value From the Veterans Affairs Clinical Assessment, Reporting, and Tracking System (VA CART) Program”

Abstract: CorrespondenceWe appreciate the interest in our article 1 by Drs Wasfy, Dominici, and Yeh. We agree with their viewpoint about the importance of reducing unnecessary readmissions following percutaneous coronary intervention in optimizing quality and eliminating unnecessary costs. However, we would like to clarify the differences in cost perspective taken by Wasfy and colleagues and our article. Wasfy and colleagues apply a Medicare reimbursement perspective in considering costs. In this payer perspective, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
(15 reference statements)
2
10
1
Order By: Relevance
“…However, our results differ from prior investigations in the VA Healthcare System (8,9). Unlike these studies, we found an association between higher risk-adjusted costs and higher readmissions and mortality.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our results differ from prior investigations in the VA Healthcare System (8,9). Unlike these studies, we found an association between higher risk-adjusted costs and higher readmissions and mortality.…”
Section: Discussioncontrasting
confidence: 99%
“…Yet prior work in this area has understudied appropriateness in its assessments. In a large population of patients undergoing PCI in the Veterans Affairs (VA) Healthcare System, investigators reported variability in outcomes and costs across hospitals, but did not assess appropriateness 9,10 . In an analysis of the National Cardiovascular Data Registry (NCDR) CathPCI registry, appropriateness of PCI was found to be uncorrelated with procedural complications in the hospital; however, no examination of post-discharge outcomes or costs was performed 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, if compensation for PCI and post-PCI care is aggregated into bundled payments, the small proportion of cost attributable to readmissions may limit provider enthusiasm for focusing on readmissions rather than index episodes of care. 11 Furthermore, PCI readmission does not appear to relate closely to procedural complications. In particular, a medical record review of 262 early PCI readmissions at Geisinger Medical Center in Danville, Pennsylvania, demonstrated that only 11.9% of readmissions are related to procedural complications.…”
Section: Limitations Of the Pci Readmission Performance Metricmentioning
confidence: 97%
“…Because the cost of PCI readmission reflects only 5.8% of the cost of total PCI episodes of care, 11 some have argued that focusing on the index PCI may offer more effective opportunities to improve value. Alternative possibilities for cost savings include reducing inappropriate PCI or limiting waste during the index episode of care.…”
Section: Limitations Of the Pci Readmission Performance Metricmentioning
confidence: 99%
“…15 The Medicare Payment Advisory Committee identified PCI as one of the seven conditions that accounted for nearly a third of the total readmission costs in the U.S. 16 Readmissions after PCI have been extensively studied previously. 12,17,18 However, the readmission rates in the high-risk subgroup of multivessel PCI in STEMI are unknown. In this context, we extend the work of prior investigators by studying the causes and factors associated with readmission in patients undergoing multivessel PCI for STEMI.…”
Section: Introductionmentioning
confidence: 99%